2015
DOI: 10.1021/ma502556n
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of Thin Polymer Films: From Linear Chain to Soft Colloid-like Behavior

Abstract: We show that the vitrification of star-shaped polystyrene (PS), of functionality f and molecular weight per arm M w arm , thin films supported by silicon oxide, SiO x , is strongly dependent on M w arm and f. When f is small, the vitrification behavior is similar to that of linear-chain PS where the average glass transition, T g , decreases with decreasing film thickness (ΔT g < 0). However, for sufficiently large f and small M w arm , T g becomes independent of film thickness (ΔT g ≈ 0). In this region, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 55 publications
(101 reference statements)
8
88
0
Order By: Relevance
“…6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film. 20 In this letter we demonstrate using XPCS that the in contrast to the linear chain polymers, the free surface layer relaxations are slow compared to the bulk and this persists to temperatures T > T g + 50 K. Molecular dynamics simulations of supported thin polymer films indicate that the slow dynamics, and Tgsurf>Tgbulk, would be due to a preferential localization of these molecules at the free surface.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film. 20 In this letter we demonstrate using XPCS that the in contrast to the linear chain polymers, the free surface layer relaxations are slow compared to the bulk and this persists to temperatures T > T g + 50 K. Molecular dynamics simulations of supported thin polymer films indicate that the slow dynamics, and Tgsurf>Tgbulk, would be due to a preferential localization of these molecules at the free surface.…”
supporting
confidence: 76%
“…Tgsurf>Tgbulk. 6,19,20 However Tgsurf became gradually lower than Tgbulk as M w arm became much larger than M e, the molecular weight between entanglements; this trend is consistent with the behavior of linear chain polymers. 6,19,20 Molecular dynamics simulations revealed that this behavior– Tgsurf>Tgbulk-might be due to positional correlations of the star-shaped molecular at the free surface of the film.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Study of polymer materials in recent years have focused on the development of advanced polymer architectures with tuneable materials properties [1][2][3][4][5] . Branched polymers are interesting because their solution 6,7 , rheological [8][9][10] and surface properties 10,11 are different to their linear analogues.…”
Section: Introductionmentioning
confidence: 99%